Sanat Eğitiminde Yeni Yaklaşımlar-1 - Gökalp, Aslı; Yerli, Serdal; Arslan, Suzan; Uz, Ayfer; Çelebi, Tuğba; Tekin Karagöz, Ceren; Güneş Aytaç, Nurhayat; Yağçı Turan, Münire Meral; Yerli, Serdal; Kılıç, Ahmet Göktuğ; Vargün, Özlem (Akademisyen Yayınevi Kitap DOI Portalı, 2024)
-